2019
DOI: 10.5897/ajbm2018.8692
|View full text |Cite
|
Sign up to set email alerts
|

Role of entrepreneurship education on students intention and mediating effect of self-efficacy

Abstract: Entrepreneurship education trend is increasing rapidly worldwide. This increase was driven through entrepreneurship promise like a catalyst to promote economic revival and growth. It is anticipated entrepreneurship education provides the basis of entrepreneurship notions, forming attitude, behavior, and mind set of the entrepreneurs. Several programs regarding entrepreneurial education established in universities have significantly increased worldwide. The objective of the study is to assess the role of entrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It aims to develop full-fledged entrepreneurs (Kim, 2017). Students who are exposed to or introduced to EE are much more likely to pursue entrepreneurial paths or occupations than students who are not introduced to EE (Yasir et al, 2019). Furthermore, a study has demonstrated that EE has a significant and observable impact on an individual's entrepreneurial perceptions, intentions and behaviours (Kisubi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It aims to develop full-fledged entrepreneurs (Kim, 2017). Students who are exposed to or introduced to EE are much more likely to pursue entrepreneurial paths or occupations than students who are not introduced to EE (Yasir et al, 2019). Furthermore, a study has demonstrated that EE has a significant and observable impact on an individual's entrepreneurial perceptions, intentions and behaviours (Kisubi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%